2021
DOI: 10.3390/foods10061431
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of the Jackfruit Seed Sourced Resistant Starch and Bifidobacterium pseudolongum subsp. globosum on Suppression of Hyperlipidemia in Mice

Abstract: Approximately 17 million people suffer from cardiovascular diseases caused by hyperlipidemia, making it a serious global health concern. Among others, resistant starch (RS) has been widely used as a prebiotic in managing hyperlipidemia conditions. However, some studies have reported limited effects of RS on body weight and blood lipid profile of the host, suggesting further investigation on the synergistic effects of RS in combination with probiotics as gut microbes plays a role in lipid metabolism. This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Although, RS obtained by food processing needs chemical-physical structure characterization [22][23][24][25][26][27][28][29][30]. To this, several techniques to determine their crystallinity, structural order, chain-length distribution and conformation, helicity, as well as double-helical structures are used [31][32][33][34][35][36][37][38]. These include: (i) scanning electron microscopy (SEM), (ii) differential scanning calorimetry (DSC), (iii) X-ray diffraction (XRD) analysis, (iv) solid-state 13 C nuclear magnetic resonance ( 13 C-NMR), (v) permethylation-GC-MS and (vi) Fourier transform infrared spectroscopy (FT-IR).…”
Section: Type Of Resistant Starch and Its Content In Mediterranean Foodmentioning
confidence: 99%
“…Although, RS obtained by food processing needs chemical-physical structure characterization [22][23][24][25][26][27][28][29][30]. To this, several techniques to determine their crystallinity, structural order, chain-length distribution and conformation, helicity, as well as double-helical structures are used [31][32][33][34][35][36][37][38]. These include: (i) scanning electron microscopy (SEM), (ii) differential scanning calorimetry (DSC), (iii) X-ray diffraction (XRD) analysis, (iv) solid-state 13 C nuclear magnetic resonance ( 13 C-NMR), (v) permethylation-GC-MS and (vi) Fourier transform infrared spectroscopy (FT-IR).…”
Section: Type Of Resistant Starch and Its Content In Mediterranean Foodmentioning
confidence: 99%
“…Differently, compared with the donkey, sampling method had more signi cently in uence on the cow. In the fecal samples, Bi dobacterium pseudolongum, predominant in cow dung and never be isolated in human feces [44], had the ability of the jackfruit seed sourced resistant starch utilization [45]. Lachnospiraceae bacterium may in uenced the development of obesity and diabetes [46].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, polyamines may be tested to prevent bone destruction associated with chronic infections in obesity/T2D, where mice at 21 days postinfection show significantly more bone loss than lean/control mice ( 47 ). We suggest that the changes in the gut microbiota, including increased B. pseudolongum abundance, likely lead to increased systemic polyamine production for several reasons: (i) experiments with various Bifidobacteria species demonstrated their capability to produce spermidine in vitro , (ii) shotgun metagenomic sequencing of gut microbiota from obese mice fed resistant starch indicated that polyamine synthesis was associated with increases in B. pseudolongum , and (iii) treatment of mice with arginine and Bifidobacterium animalis led to increased levels of circulating and colonic polyamines, which corresponded with decreased levels of TNF-α and IL-6 ( 76 78 ). The evidence from our work demonstrated that polyamines were significantly upregulated in the gut, where microbes are abundant ( Fig.…”
Section: Discussionmentioning
confidence: 99%